The nexus between financial development and human development: the case of developing countries / Bilgehan Tekin - Tekin, Bilgehan (Universiti Teknologi Mara Selangor, 2020)
The purpose of this study is to examine the relationship between financial development and human development from the health and welfare dimensions of developing countries. This study aims to determine whether the financial developments of the countries have an effect on the basic human development of the individuals and whether human development indicators have an impact on financial development. In this study, the relationship between financial development and human development were revealed by using data obtained from developing countries. The financial development levels of countries was measured using the financial development index. The index is calculated by using M3 / GDP, private sector loans / GDP and loans to banks from private sector / GDP ratios. The human development index is calculated by considering various health indicators and GNP per capita. The data includes annual data for the period 1970- 2016. Pedroni and Kao cointegration analysis and Dumitrescu and Hurlin panel causality analysis were performed in the study. The results show that there is long-term cointegration relationship and two-way causality between financial and human development in developing countiries.